PENGARUH MODEL STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR PKn DI SEKOLAH DASAR - Safitri, Yani; Sabri, Tahmid; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to see the effect of the implementation of model student team achievement division on civics lesson scores and analyze how much the effect of student teams achievement division model implementation on civics lesson scores for third-grade students of Public Elementary School 34 Pontianak Kota. This study used a quasi-experimental experiment method, with an experimental design of Non-Equivalent Control Group Design. The population in this study is all third-grade students of Public Elementary School 34 Pontianak Kota. Subjects in this study are whole students of the third class of E which are 32 students as an experimental class and third class of A which are 31 students as a control group/class. Data collection techniques used are measurement techniques, with data collection tools in the form of 35 objective tests. Then the analysis is done using the t-test. Based on the results of the analysis obtained t_count (3,391)> t table (1,676) then Ha is accepted. So it can be concluded that there are differences in civics lesson scores between students who used the Student Teams Achievement Division Model and students who did not use the Student Teams Achievement Division Model. From the calculation of the effect size obtained ES of 0.62 (medium criteria). It means learning by implementing the Student Teams Achievement Division Model gives moderate effect on student civics lesson score for third-grade students of Public Elementary School 34 Pontianak Kota.Â Keywords: The Effect, Theory Of Model Student Team Achievement Division, Civics Lesson Scores.